METHODS FOR THE DEVELOPMENT OF PEDAGOGICAL COMPETENCE OF FUTURE PHYSICS TEACHERS - Yulduz Khairullakizi Hudoyberdiyeva (Journal Park Publishing, 2023)
This article will talk about the didactic possibilities of developing the logical competency of future physics teachers. The article provides feedback from various scientific bases.
Keywords: educational process, competence, competence, competency approach.